2020
DOI: 10.5334/aogh.2725
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Wood Smoke and Associated Health Effects in Sub-Saharan Africa: A Systematic Review

Abstract: Background: Observational studies suggest that exposure to wood smoke is associated with a variety of adverse health effects in humans. Objective: We aimed to summarise evidence from sub-Saharan Africa on levels of exposure to pollutants in wood smoke and the association between such exposures and adverse health outcomes. Methods: PubMed and Google scholar databases were searched for original articles reporting personal exposure levels to pollutants or health outcomes associated with wood smoke exposure in Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 83 publications
(236 reference statements)
0
20
0
1
Order By: Relevance
“…Emissions from biomass fuel are widely recognised as a major health concern and have been associated extensively with pulmonary and cardiovascular diseases [ 7 , 32 ]. Our study observed breathing difficulties amongst the participants, with some participants indicating more difficulties when cooking with wood, which is consistent with research on a larger population sample in Malawi [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emissions from biomass fuel are widely recognised as a major health concern and have been associated extensively with pulmonary and cardiovascular diseases [ 7 , 32 ]. Our study observed breathing difficulties amongst the participants, with some participants indicating more difficulties when cooking with wood, which is consistent with research on a larger population sample in Malawi [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Para Colombia, existe un gran reto en términos de formulación de estrategias e intervenciones para reducir la exposición al humo de tabaco y al humo de leña en favor de la salud materna e infantil (25), pues la evidencia científica es contundente frente a los beneficios de un ambiente libre de humo. En Inglaterra, este tipo de medidas logró un impacto beneficioso estimado inmediato en los resultados de los nacimientos en general (26).…”
Section: Discussionunclassified
“…Exposure to household air pollution in adults has been associated with various diseases such as chronic obstructive pulmonary disease (COPD), asthma, cancers of the lungs and nasopharynx, stroke, ischemic heart diseases and diseases of the eye [ 1 , 3 , 7 , 8 , 9 , 10 ]. It is also associated with low birth weight and, of particular concern, acute lower respiratory infections such as pneumonia among children less than five years of age [ 1 , 4 , 11 , 12 ]. In total, nearly four million premature deaths per year from illnesses attributable to household air pollution are reported globally [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…High indoor PM 2.5 concentration is still a problem in various parts of the world [ 14 ], far exceeding the given limits in countries where a large proportion of the population depends on solid fuel use for cooking and heating [ 15 ]. Together with the population growth in the Sub-Saharan Africa region [ 16 ], the problem of household air pollution and related health problems, including the negative association of this with life expectancy in the long term [ 17 ], puts Sub-Saharan Africa singularly at a higher risk, when compared with other parts of the world [ 12 , 18 ].…”
Section: Introductionmentioning
confidence: 99%